PSYCHOLOGICAL PRINCIPLES OF TEACHING ENGLISH (Innovative Technologica: Methodical Research Journal, 2023)
This article discusses the basic principles of using integrated language skills in teaching English. When we integrate things, they interact or work together to be more effective. An integrated system increases the level of usefulness by bringing different ideas together in one way.